Evaluation of PCDD/Fs, dioxin-like PCBs and PBDEs in sperm whales from the Mediterranean Sea - Bartalini, A.; Muñoz-Arnanz, J.; Marsili, L.; Mazzariol, S.; Fossi, M. C.; Jiménez, B. (BMC Evolutionary Biology, 2019)
Numerous studies to date have reported concentrations of Persistent Organic Pollutants (POPs) in different marine mammal species worldwide. Yet data on sperm whales are scarce from rich and unique biodiverse areas such as the Mediterranean Sea. This work aimed to assess levels of dioxin-like polychlorinated biphenyls (dl-PCBs), polybrominated diphenyl ethers (PBDEs), and polychlorodibenzo-p-dioxins and furans (PCDD/Fs) in blubber of sperm whales stranded along the Italian coast between 2008 and 2016. POP mean concentrations (dl-PCBs: 6410 ng/g l.w.; PBDEs: 612 ng/g l.w.; PCDD/Fs: 57.8 pg/g l.w.) were mostly in line with what has been previously reported on the same species in the Mediterranean environment and tended to be higher than those reported from other geographical regions. The relative abundance followed the order dl-PCBs > PBDEs ≫ PCDD/Fs. Interestingly, the non-ortho dl-PCB pattern (126 > 169 > 77) was similar to that described in other studies worldwide and different from what is described in its main prey. This could be linked to particular metabolic activities in sperm whales against these highly toxic contaminants. Total TEQs ranged from 275 to 987 pg/g l.w. and showed the pattern Σnon-ortho-dl-PCBs > Σortho-dl-PCBs > PCDDs > PCDFs, with PCBs’ contribution about 96%. These findings highlight the high abundance of PCBs still found in the Mediterranean environment despite having been banned for decades. All sperm whales analyzed in this study surpassed the threshold of 210 pg WHO-TEQ/g l.w. proposed as starting point of immunosuppression in harbour seals; a level of contamination that may have contributed to an impairment of their immune system.